A Systematic Review of the Extent, Nature and Likely Causes of Preventable Adverse Events Arising From Hospital Care - A Akbari Sari; L Doshmangir; T Sheldon (Tehran University of Medical Sciences, 2010)
"nBackground: Understanding the nature and causes of medical adverse events may help their prevention. This systematic review explores the types, risk factors, and likely causes of preventable adverse events in the hospital sector."nMethods: MEDLINE (1970-2008), EMBASE, CINAHL (1970-2005) and the reference lists were used to identify the studies and a structured narrative method used to synthesise the data."nResults: Operative adverse events were more common but less preventable and diagnostic adverse events less common but more preventable than other adverse events. Preventable adverse events were often associated with more than one contributory factor. The majority of adverse events were linked to individual human error, and a significant proportion of these caused serious patient harm. Equipment failure was involved in a small proportion of adverse events and rarely caused patient harm. The proportion of system failures varied widely ranging from 3% to 85% depending on the data collection and classification methods used."nConclusion: Operative adverse events are more common but less preventable than diagnostic adverse events. Adverse events are usually associated with more than one contributory factor, the majority are linked to individual human error, and a proportion of these with system failure.